Numerical simulation of liquid sloshing phenomena in partially filled containers - Chen, Y.G.; Djidjeli, K.; Price, W.G. (Computers & fluids, 2009)
In the simulation of the dynamic load excited by sloshing in a partially filled tank, appropriate boundary conditions need imposing to calculate the impact pressure. Traditionally, a thin artificial buffer zone is adopted near the tank ceiling and a linear combination of free surface dynamic and rigid wall boundary conditions are imposed inside the buffer zone. This investigation demonstrates that no special treatment is needed to describe the free surface, because a two-fluid approach based on a level set method is used to solve the Reynolds-averaged Navier–Stokes (RANS) equations in both water and air regions and the interface is treated as a variation of the fluid properties. All the boundary conditions adopted are those usually accepted in solutions of Navier–Stokes or Euler equations. Sloshing in a rectangular tank excited by a horizontal harmonic motion is assessed numerically at different filling levels and excitation frequencies. The dependency of numerical solution on grid resolution, time step size and the interface thickness are investigated. Further, numerical tests are conducted for a rectangular tank with both 45° and 60° chamfered ceiling corners subject to a harmonic rolling motion. The comparison of computed results with experimental data show the developed numerical method is capable of the simulation of dynamic pressure loads exerted on the tank walls and ceiling excited by fluid sloshing.